PENGAMBA’ : ROLE AND CONTRIBUTION TO INDONESIA FISHING COMMUNITIES: - - Sofia; Subekti, Sri; Sunartomo, Aryo Fajar (International Journal of Research -GRANTHAALAYAH, 2023)
Pengamba’ is an actor in fishing community that has important and strategic roles especially in the social and economic activities. This research conducted in June – September 2022 in Jember Regency with two objectives: 1) to identify the position, role, and contribution of pengamba’ in the fishing community; 2) to identify the strategy used by pengamba’ to face the bussiness competition with the other pengamba’. This research used descriptive and qualitative method. The result of the research shows that pengamba’ has important role manifested in three forms of collaboration, namely collaboration in providing capital, collaboration in marketing, and collaboration in social acivity. The most dominant role of pengamba’ in fisherman’s economic activity is in providing capital and marketing of fish. This condition causes the high dependency of fisherman to pengamba’. The main strategy to maintain and to develop their bussiness is providing good service to the fishermen as the main customers.